Teachers of Punjabi Sikh Ancestry: Their Perceptions of Their Roles in the British Columbia Education System - Hirji, Shemina; Beynon, June (Alberta Journal of Educational Research, 2000)
This study examines the perceptions of teachers of Punjabi Sikh ancestry of their roles in the British Columbia public education system. Twenty teachers, 13 females and seven males, were interviewed. Three of the participants were born in Canada, 17 had immigrated to Canada. The participants ranged in age from their early 20s to their late 40s. The results of this investigation indicate that these teachers see themselves playing a wide range of roles in the education system. They recount that they serve as bridges between the Punjabi Sikh community and the education system, acting as translators, cultural informants, and role models. These teachers are also committed to influencing selected cultural values of Punjabi Sikh parents in order to reflect mainstream attitudes toward education and gender roles. This research has important implications for teacher education programs and public school districts that recruit, train, and employ minority teachers. This research suggests that it is critical to acknowledge teachers of Punjabi Sikh ancestry not just as "professional ethnics," but as educators with a range of skills and talents as varied as those of their mainstream colleagues.